2009
DOI: 10.1080/08860220802595500
|View full text |Cite
|
Sign up to set email alerts
|

Icodextrin Dialysate Improves Nutritional and Inflammatory Profiles in Peritoneal Dialysis Patients

Abstract: Background. Previous studies demonstrate that icodextrin is superior to 4.25% dextrose for fluid removal in patients with high and high-average transport membrane. Recent studies reveal that controlling volume status improves malnutrition in peritoneal dialysis (PD) patients. This study hypothesized that icodextrin enhances nutritional and inflammatory status by improving fluid balance. Methods. This retrospective case-control study investigated the effects of icodextrin on patient nutritional profiles over a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Martikainen et al showed that Icodextrin use was resulted in subclinical inflammatory response [11]. In contrast, Lin et al reported that Icodextrin decreased CRP [12]. In this study the basal serum CRP and fibrinogen levels were similar and elevated in both study groups ( Table 3).…”
Section: Discussionsupporting
confidence: 43%
See 2 more Smart Citations
“…Martikainen et al showed that Icodextrin use was resulted in subclinical inflammatory response [11]. In contrast, Lin et al reported that Icodextrin decreased CRP [12]. In this study the basal serum CRP and fibrinogen levels were similar and elevated in both study groups ( Table 3).…”
Section: Discussionsupporting
confidence: 43%
“…The effects of Icodextrin on inflammation status in PD patients are controversial [11,12]. Martikainen et al showed that Icodextrin use was resulted in subclinical inflammatory response [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of 22 patients, Martikainen et al (55) showed that there was an increase in serum C-reactive protein (CRP) levels, as well as dialysate IL-6 and TNF alpha with 8 weeks of icodextrin use. However, in another study comparing 32 PD patients using icodextrin to 10 patients not using icodextrin, the inflammatory marker highsensitivity CRP decreased significantly only in the icodextrin group (P ϭ 0.0048) (56). In a series of eight anuric patients from Japan who were switched from glucose solutions to icodextrin (long-dwell exchange), the effluent leukocyte counts and fibrin degradation products were increased at 12 and 36 weeks after the switch to icodextrin, whereas IL-6 and CA-125 levels stayed the same (57).…”
Section: Icodextrin Pd Solutionmentioning
confidence: 99%
“…Experimental evidence indicates that serum CRP levels increased during PD (32)(33)(34). Glucose and glucose degradation products in the PD solutions can increase CRP levels of PD patients (35,36). CRP is known to positively correlate with cardiovascular events and mortality in PD patients (3,7,(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%